Analisis Strategi Pengembangan Usaha Pondok Pesantren Dalam Upaya Mewujudkan Kemandirian Ekonomi Pesantren Dalam Perspektif Suistainable Development Goals (SDGS) Studi Kasus Pada Koperasi Pondok Pesantren Sa’adatuddarein Kota Jambi - M. Marwan Mahdi; Rafiqi; Lucky Enggraini Fitri (JOURNAL OF SHARIA ECONOMICS, 2024)
This study aims to analyze the business development strategy of Pondok Pesantren Sa’adatuddarein Jambi City in an effort to achieve the economic independence of the Islamic boarding school from the perspective of Sustainable Development Goals (SDGs). This research employed a qualitative approach with a case study method at the Islamic Boarding School Cooperative (KOPONTREN) of Pondok Pesantren Sa’adatuddarein Jambi City. Data collection techniques were conducted through observation, in-depth interviews, and documentation involving cooperative managers, pesantren administrators, and business actors within the pesantren environment. Data were analyzed descriptively using qualitative analysis and strengthened by SWOT analysis through IFAS and EFAS matrices to identify internal and external factors in the development of pesantren business enterprises. The results of the study indicate that the business development strategy of KOPONTREN is implemented through strengthening institutional management, optimizing the internal resources of the pesantren, increasing students’ involvement in productive economic activities, and expanding business networks and partnerships. Based on the SWOT analysis, KOPONTREN is positioned in the aggressive strategy quadrant (growth oriented strategy), indicating that the pesantren possesses significant strengths and opportunities to develop its business sustainably. The development of the pesantren cooperative business contributes to supporting the economic independence of the pesantren and is relevant to the achievement of Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 4 (Quality Education), and SDG 8 (Decent Work and Economic Growth).